Labour History and the Interlocking Hierarchies of Class, Ethnicity, and Gender: A Canadian Perspective - Frager, Ruth A. (International Review of Social History, 1999)
This paper develops the concept of interlocking hierarchies [within the working class] by focusing on the Canadian situation. While emphasizing the complex dynamics of worker resistance and adaptation, the paper briefly examines the shortcomings of Canadian working-class historiography. The paper then explores the significance of interlocking hierarchies and sketches the ways in which this analytical framework can be applied, first by emphasizing gender issues and secondly by emphasizing ethnicity in the Canadian context, particularly in the late nineteenth and early twentieth centuries. (I use the term ‘‘ethnicity’’ broadly in order to avoid using the term ‘‘race’’ as much as possible, so as not to lend credence to the notion that ‘‘race’’ represents a fixed biological category.) In emphasizing ethnicity, the paper focuses first on issues concerning immigrant workers from Asia and then on issues concerning immigrant workers from southern and eastern Europe. –From author's introduction